Clinical characteristics, depression, anxiety, and stress of medical workers during the COVID-19 pandemic: a cross-sectional survey - Li, Xue; Zhang, Qian; Li, Wenkun; Wei, Jian; Xing, Jie; Yang, Xun; Li, Peng; Zhang, Shutian (The Journal of Infection in Developing Countries, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) has an extremely high infection rate. This study aimed to investigate emotional states and COVID-19 infection of medical workers during the self-management strategy to COVID-19. Methodology: Questionnaires were collected via an online questionnaire platform from 20 December 2022 to 19 January 2023, including demographic characteristics, number of vaccine doses, COVID-19 test results, occupation, attendant situations of workers, clinical symptoms, disease duration, and the Depression, Anxiety and Stress Scale 21. Results: A total of 748 complete questionnaires were collected. The average age of participants was 33.61 ± 8.94 years, and 79.55% participants were female. The proportion of anxiety was significantly higher in the infection group (52.32%) than in the non-infection group (28.45%) (p < 0.001), as was the proportion of stress (41.47% vs. 31.90%, p = 0.046). Medical students (odds ratios (OR) 0.54, 95% confidence interval (CI) 0.31–0.93) and other staff (OR 0.63, 95% CI 0.40–0.98) had a lower risk for depression than doctors (p = 0.024), and attendant and infective situations of workers was the risk factor for depression (p = 0.007). Occupation (p = 0.029) and infected workers (p = 0.001) were related to anxiety. Infected attendant workers had a higher risk for stress (OR 1.97, 95% CI 1.12–3.48) than uninfected attendant workers (p = 0.019). Conclusions: Most medical workers infected with COVID-19 had emotional disorders during the COVID-19 pandemic. Attention and useful measures are suggested to support medical workers.